Perception of the effects of drug use among adolescents - Sandu, Mihaela Luminita; Rus, Mihaela; Rus, Ciprian Vasile (Technium Social Sciences Journal, 2020)
At the global level, drug use and trafficking are a dynamic phenomenon, being strongly influenced by a multitude of social and economic factors. and in Romania, drug use and trafficking present new forms of manifestation, requiring increasingly varied approaches, being known as a complex phenomenon, characterized by permanent mutations. If, some twenty years ago, Romania was known as a state where only drugs were transited, in the last ten years, our country has been transformed into a market for drug use, especially heroin. Even though our country is below the European average for drug use, the latest studies conducted by the National Drug Agency indicate a lifetime prevalence of 4.3% for any type of drug in the general population, while among the population for 16-year-old students, this type of prevalence stands at 10%, which shows significant increases in drug use in Romania, at the level of the entire population, but especially among the young.